Efektivitas Komunikasi Verbal dan Non Verbal Dalam Komunikasi antar Budaya - christian purba; Chontina Siahaan (Prodi Sastra Inggris UKI, 2022)
Communication develops in line with increasingly advanced technology. Communication carried out by the community is only limited to talking regardless of whether the interaction is effective or not. This research was conducted to find out the communication patterns that are usually carried out by the people of East Jakarta, represented by thirty-seven participants with sixteen of them being students of the Indonesian Christian University. Using the questionnaire method to obtain data this research uses a qualitative approach with a descriptive method. The results showed that the communication pattern of the people of East Jakarta had a habit of using verbal methods combined with nonverbal methods. This is done because he wants the message conveyed orally or in writing to be clearly received and the feelings or emotional messages from the communicator are conveyed properly. Thirty-two people admitted that they often interacted with people from different cultures with various interaction locations, namely schools, cafes, campuses, social media, churches, and even while playing video games. In intercultural communication conducted by participants with a percentage of 81.1% with 30 people claiming to prefer using Indonesian because it makes it easier to interact, but in contrast to participants who prefer to adapt their language to the other person. This is done to provide a sense of comfort to the communicant in interacting.